Characterization of the out-of-plane Dresselhaus effective magnetic field in InGaAs/InAlAs (110) multiple quantum wells at room temperature. (1st April 2023) - Sato, Shota; Sugaya, Kyohei; Nakanishi, Koichi; Yokota, Nobuhide; Kohda, Makoto; Morita, Ken
Abstract: Recently, we directly observed the out-of-plane Dresselhaus spin–orbit (SO) interaction field and extracted the SO coefficient β from InGaAs (110) quantum wells (QWs). However, the extracted β was much larger than that of the (001) QWs, which yielded an in-plane Dresselhaus SO field. In this study, we perform Monte-Carlo simulations and reproduce the results of time-resolved and spatiotemporally resolved Kerr rotation measurements in InGaAs (110) QWs. The results conclusively show that InGaAs (110) QWs have a strong out-of-plane Dresselhaus SO field as compared with (001) QWs.